Normal-temperature preparation method of quartz ore inclusion detection sample
Through optical screening and room temperature cutting and polishing processes, the problems of high cost, high energy consumption and high sample damage rate of quartz ore inclusion detection equipment have been solved, and low-cost and efficient sample preparation has been achieved, which is suitable for rapid detection in grassroots laboratories.
Patent Information
- Application Number
- CN202511062478.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-31
- Publication Date
- 2025-10-17
AI Technical Summary
Existing quartz ore inclusion detection equipment is expensive, energy-intensive, complex to operate, and has a high sample damage rate, making it difficult to popularize in grassroots laboratories. Traditional low-temperature polishing processes can easily cause inclusion rupture or phase change, posing an environmental pollution risk.
Optical screening is used instead of XRD positioning, diamond-coated thin-blade saw blades are used for low-speed cutting with water-based coolant, three-level chemical mechanical polishing is performed at room temperature, combined with ultrasonic cleaning and room-temperature heat treatment, and the liquid nitrogen refrigeration system is eliminated.
The equipment cost is significantly reduced to less than 50,000 yuan, the energy consumption is reduced to 0.8kW/h, the inclusion integrity rate is increased to 89.5%, the operation is simplified, and it is suitable for grassroots laboratories to meet the needs of rapid testing.
Smart Images

Figure CN120800942A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of mineral analysis and sample preparation, and particularly relates to a normal-temperature preparation method of a quartz ore inclusion detection sample. BACKGROUND
[0002] Quartz ore inclusion detection is an important link in geological exploration and mineral analysis, and the sample preparation technology thereof directly affects the accuracy and reliability of the detection result. Traditional quartz inclusion sample preparation technology usually relies on X-ray diffraction (XRD) or laser scanning equipment to accurately position the inclusion enrichment area, and then uses a diamond wire saw to cut, and needs to be polished at a low temperature below-20 DEG C to reduce the damage of friction heat to the inclusion. A typical device structure comprises a high-precision detection module, a liquid nitrogen-cooled low-temperature cutting chamber and a constant-temperature controlled polishing unit, and the whole system has high integration and complex operation.
[0003] The prior art device has high cost, the introduction of the XRD positioning module and the liquid nitrogen cooling system makes the whole device cost more than 500,000 yuan, so that it is difficult for the primary laboratory to popularize; meanwhile, the prior art has high energy consumption, the continuously running refrigeration system for low-temperature polishing has an energy consumption of 2.5 kW / h, and the operation is complex and requires strict technical personnel; the traditional high-speed cutting and polishing process is easy to cause the inclusion to be broken or phase changed due to mechanical stress and friction heat, and the sample qualification rate is less than 80%; the liquid nitrogen cooling system has a leakage risk, and improper treatment of the waste abrasive material may also cause environmental pollution; the root cause of these problems lies in that the prior art excessively relies on high-precision equipment and low-temperature environment control, and fails to design a low-damage process chain suitable for the physical properties (such as optical transparency and brittleness) of quartz materials.
[0004] Therefore, in view of the above problems, the present application provides a normal-temperature preparation method of a quartz ore inclusion detection sample, which replaces the expensive XRD positioning with optical screening, optimizes the cutting and polishing process to reduce the mechanical stress, and completes the sample preparation at a normal temperature, so as to significantly reduce the cost, improve the efficiency, and ensure the integrity of the inclusion and the accuracy of the detection. SUMMARY
[0005] In order to overcome the problems of high equipment cost, high energy consumption and complex operation of the traditional technology, the present application provides a normal-temperature preparation method of a quartz ore inclusion detection sample.
[0006] The technical scheme of the present application is as follows: a normal-temperature preparation method of a quartz ore inclusion detection sample, comprising the following steps: S1, observing the light scattering mode of the sample surface by an optical microscope, and screening out the inclusion enrichment area; S2, using a diamond-coated thin blade saw blade to cut at a low speed, and cooperating with a water-based cooling liquid to reduce the friction temperature rise; S3, tertiary chemical mechanical polishing is carried out at room temperature, and diamond grinding disc, soft polishing sand paper and fiber polishing pad and diamond suspension are used in sequence for polishing; S4, the sample is placed in a constant temperature environment of 40℃ for 2 hours to release residual stress; S5, surface residues are removed by ultrasonic cleaning.
[0007] As preferred, in the optical screening stage, the gas-liquid inclusions present cloudy bright spots due to the difference in refractive index, and the solid inclusions show dark shadow areas with clear boundaries, and a strong light flashlight can be optionally provided to verify the suspected inclusion area.
[0008] As preferred, in the cutting stage, the thickness of the diamond-coated thin blade saw blade is ≤0.5mm, and a shock-absorbing smooth pushing base is used to control the mechanical vibration amplitude within 10μm.
[0009] As preferred, the specific steps of the tertiary chemical mechanical polishing include: A1, 75μm, 54μm and 18μm diamond grinding discs and RO water are used to remove macroscopic scratches; A2, 12.5μm soft polishing sand paper is used to refine the surface; A3, fiber polishing pad and 9μm, 3μm and 1μm diamond suspension are used to make the sample atomically smooth.
[0010] As preferred, the following steps are further included: B1, the polished surface is adhered to a glass slide with epoxy resin, and heated and cured at 70℃ for 3-5 hours; B2, after natural cooling to room temperature, the other untreated side is polished repeatedly; B3, surface residues are removed by ultrasonic cleaning, and the double-sided treatment is completed.
[0011] As preferred, the diamond-coated thin blade saw blade is cut at a low speed of 800-1200rpm.
[0012] As preferred, the water-based cooling liquid is a polyethylene glycol-containing aqueous solution.
[0013] As preferred, the method uses a visible light screening module, which includes a 200x optical microscope, a rotatable sample stage and a UV LED light source, and the optical characteristics of the sample surface are observed in real time through an ocular lens or a camera.
[0014] As preferred, the saw blade spindle of the diamond-coated thin blade saw blade is connected to a speed regulation motor through a belt drive, a smooth and stable guide rail base is installed at the bottom, and the cooling liquid pipeline is arranged along both sides of the saw blade.
[0015] As preferred, the method is completed at normal temperature, energy consumption is less than or equal to 0.8 kW / h, and the inclusion body integrity rate is greater than or equal to 89.5%.
[0016] The beneficial effects of the present application are: 1. The present application uses visible light screening technology to replace traditional XRD or laser positioning equipment, and cancels the expensive low-temperature control system, so that the cost of the whole preparation equipment is reduced from more than 500,000 yuan in the traditional scheme to less than 50,000 yuan, greatly reducing the technical threshold, and enabling primary laboratories and geological exploration units to easily popularize and apply.
[0017] 2. By optimizing the cutting and polishing process, the present application completely cancels the liquid nitrogen refrigeration system, and only needs a normal temperature environment to complete sample preparation, the energy consumption is reduced from 2.5 kW / h in the traditional method to 0.8 kW / h, the energy saving rate is 68%, and it is more in line with the development trend of green and low carbon.
[0018] 3. By using low-speed cutting, water-based cooling liquid and staged polishing process, the damage of mechanical stress and friction heat to the inclusion body is effectively reduced, the inclusion body integrity rate is increased from 76.3% in the traditional method to more than 89.5%, and the reliability of the detection data is significantly improved.
[0019] 4. The present application uses a standardized preparation process, and the operator can quickly master it without special training, the single batch processing time is shortened by 40% compared with the traditional method, which is suitable for rapid sampling and batch detection requirements, and improves the work efficiency of the laboratory.
[0020] 5. By optimizing the fixing and polishing process, the present application can stably process quartz thin sheet samples with a thickness of less than 0.2 mm, solving the problem of damage of ultra-thin samples caused by lack of effective fixing reference in the traditional method, and expanding the application range of the technology.
[0021] 6. The single clamping double-sided polishing technology is adopted, the total time consumption is shortened by 35% compared with the traditional step-by-step operation, and the optical screening and normal temperature polishing are combined, so that the whole sample preparation process is more efficient, thereby meeting the demand of modern laboratory for rapid detection. BRIEF DESCRIPTION OF DRAWINGS
[0022] Figure 1 The working flowchart of the present application is shown. DETAILED DESCRIPTION
[0023] In order to make the purposes, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be described clearly and completely below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are some but not all of the embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by a person of ordinary skill in the art without creative work fall within the protection scope of the present application.
[0024] The present application provides an embodiment: a normal temperature preparation method of a quartz ore inclusion detection sample, comprising: Observe the light scattering mode of the sample surface by optical microscopy, and screen out the inclusion enrichment area; Use a diamond-coated thin blade saw blade for low-speed cutting, and cooperate with a water-based cooling liquid to reduce the friction temperature rise; Carry out three-stage chemical mechanical polishing at normal temperature, and polish with diamond grinding disc, soft polishing sandpaper and fiber polishing pad and diamond suspension liquid in turn; Place the sample in a 40℃ constant temperature environment for 2 hours to release residual stress; Remove the surface residues by ultrasonic cleaning.
[0025] Please refer to Figure 1 Further, the specific implementation process of the present application can be divided into five main stages of optical screening, cutting, grading polishing, post-processing and secondary processing, which will be described in detail as follows: Further, the optical screening stage is described as follows: Firstly, place the quartz ore sample to be measured on the rotatable sample stage of the 200 times optical microscope, turn on the ultraviolet LED light source to assist observation, and observe the light scattering mode of the sample surface in real time through the ocular lens or camera. The gas-liquid inclusions present cloud-shaped bright spots due to the difference in refractive index, and the solid inclusions show clear boundary dark shadow areas. For the suspected inclusion area that is difficult to distinguish, a strong light flashlight can be used for verification irradiation. This stage does not need to rely on expensive XRD or laser positioning equipment, and the inclusion enrichment area can be accurately identified only by ordinary optical equipment, which provides accurate positioning for subsequent processing.
[0026] Further, the cutting stage is described as follows: After confirming the position of the inclusion, the sample is fixed on a shock-absorbing smooth pushing base, and cutting is performed at a low rotating speed of 800-1200 rpm by using a diamond-coated thin blade saw blade with a thickness of less than or equal to 0.5 mm, and during the cutting process, the two sides of the saw blade are accurately sprayed with a water-based cooling liquid containing polyethylene glycol, so as to effectively control the friction temperature rise, and at the same time, the mechanical vibration amplitude is strictly controlled within 10 μm by the shock-absorbing base, so as to avoid the mechanical stress damage caused by traditional high-speed cutting, and the process is performed at room temperature, so that the use of the liquid nitrogen cooling system is completely avoided, which not only reduces the energy consumption but also eliminates the safety hazards of low-temperature operation.
[0027] Further, the grading polishing stage is described in detail as follows. The cut sample is subjected to three-stage chemical mechanical polishing at room temperature: firstly, 75 μm, 54 μm and 18 μm particle size diamond grinding discs are used in turn to remove macroscopic scratches in combination with RO water, then 12.5 μm soft polishing sandpaper is used to further refine the surface, and finally ultimate polishing is performed by using a fiber polishing pad and a diamond suspension (with a gradient of 9 μm, 3 μm and 1 μm), so as to realize an atomic-level flat surface, and deionized water is used for cleaning after each polishing stage, so as to ensure that there is no abrasive residue, and the process effectively avoids the problems of inclusion thermal damage or rupture caused by traditional single polishing by gradually reducing the abrasive particle size and optimizing the polishing pressure.
[0028] Further, the post-processing stage is described in detail as follows. The sample after preliminary polishing is placed in a constant temperature environment of 40°C for 2 hours to fully release the internal residual stress, and then ultrasonic cleaning is performed at a frequency of 40 kHz for 15 minutes to completely remove the residual abrasive particles and polishing liquid on the surface, and the low-temperature heat treatment specially designed in this stage not only avoids the phase transition of the inclusion that may be caused by high-temperature annealing, but also significantly improves the structural stability of the sample, thereby providing reliable guarantee for subsequent detection.
[0029] Further, the fixing and secondary processing stage is described in detail as follows. The polished surface is uniformly coated with epoxy resin, and after being attached to a glass slide, it is placed on a heating table at 70°C for curing for 3-5 hours, and after natural cooling for 6-8 hours to room temperature, the sample is turned over, the above-mentioned three-stage polishing process is repeated on the untreated surface, and finally ultrasonic cleaning is performed again to obtain a finished product with double polished surfaces, and the innovative single clamping double-sided processing technology shortens the working hours by 35% compared with the traditional step-by-step operation, and is especially suitable for processing ultra-thin samples with a thickness of less than or equal to 0.2 mm.
[0030] Further, the present application provides an embodiment of a standard double-sided processing. Select a quartz sample containing rich gas-liquid inclusions, and perform optical screening according to the above process. The sample is cut by a 0.3mm thick diamond saw blade (1000rpm), and the total polishing time is 4 hours. After the epoxy resin is cured, the inclusion integrity is 93.1%, and the surface roughness Ra is less than or equal to 5nm, which fully meets the requirements of high-resolution microscopy observation.
[0031] A quartz sample containing rich gas-liquid inclusions is selected, and X-ray fluorescence spectroscopy (XRF) is used to preliminarily analyze the SiO2 content of the sample, which is greater than or equal to 99.5%, and the sample contains rich gas-liquid inclusions. The surface of the sample is cleaned by ultrasonic cleaning with alcohol to remove attached contaminants, and then dried with nitrogen for standby.
[0032] Place the sample on the stage of a 200x optical microscope, and turn on the UV LED auxiliary light source. Through the ocular lens, it is found that the upper left area of the sample presents a typical cloud-like bright spot, and the lower right area is distributed with clear dark shadow areas. The use of a strong light flashlight at an oblique angle verifies that the inclusion density of the target area meets the detection requirements.
[0033] A 0.3mm thick diamond-coated saw blade is used, and the spindle speed is set to 1000rpm and the feed speed is 0.2mm / s. During the cutting process, a water-based coolant containing 5% polyethylene glycol is continuously sprayed. The infrared temperature measurement shows that the cutting interface temperature is always maintained at 28±2℃. The vibration amplitude is controlled at 8μm by the shock absorbing base. The flatness of the cut sample is ±2μm.
[0034] Then, rough polishing is performed using a 75μm diamond grinding disc with RO water flushing, which takes 30 minutes to remove cutting marks. Then, medium polishing is performed using 54μm and 18μm diamond grinding discs, each for 20 minutes, and the surface roughness is reduced to Ra 0.1μm. Finally, fine polishing is performed using a fiber polishing pad + 1μm diamond suspension, and an atomic-level flat surface is obtained after 40 minutes of treatment.
[0035] After the sample is placed in a 40℃ constant temperature oven for 2 hours, epoxy resin is uniformly coated on the polished surface, and is attached to a 1mm thick glass slide. The sample is heat-cured at 70℃ for 4 hours, and the cooling time is 7 hours. After turning over, the same polishing process is repeated on the back surface. The total processing time is reduced by 38% compared with the traditional method.
[0036] The prepared sample is detected by a laser confocal microscope, and the inclusion integrity is 93.1%. Further, the present application provides an embodiment of ultra-thin sample processing: For a quartz sheet with a thickness of 0.15mm, a high-adhesion petrographic epoxy resin + curing agent combination is used. During the second polishing, the temperature of the glass slide is stably controlled at 42℃ by the air cooling system. The final sample has no warping deformation, and the edge integrity is 91.4%. This breaks through the technical bottleneck of the traditional method of processing ultra-thin samples which is prone to damage.
[0037] Further, the present application provides an embodiment of a rescue preparation of a fissure sample: When processing a quartz sample with microfissures caused by geological stress, first inject a low-viscosity penetrating epoxy resin to fill the fissures before cutting, and after curing, use a "slow feed-low speed" cutting mode (feed speed 0.1 mm / s, speed 600 rpm), and use an elastic polishing pad to buffer mechanical stress in the polishing stage, and finally control the sample fissure expansion rate within 3%, thereby achieving the rescue preparation of a defective sample.
[0038] Through the above steps, by using visible light screening technology instead of traditional XRD or laser positioning equipment, and by canceling the expensive low-temperature control system, the cost of the entire preparation equipment is reduced from more than 500,000 yuan in the traditional scheme to less than 50,000 yuan, greatly reducing the technical threshold, enabling primary laboratories and geological exploration units to easily popularize and apply, and solving the problems of high equipment cost, high energy consumption and complex operation of traditional technology.
Claims
1. A method for preparing a quartz ore inclusion detection sample at room temperature, characterized in that: Includes: S1, observe the light scattering pattern of the sample surface through an optical microscope and screen out the inclusion-rich area; S2, uses a diamond-coated thin-edged saw blade for low-speed cutting, combined with water-based coolant to reduce friction temperature rise; S3, three-stage chemical mechanical polishing at room temperature, using diamond grinding disc, soft sandpaper and fiber polishing pad with diamond suspension for polishing in sequence; S4, placing the sample in a constant temperature environment at 40 °C for 2 hours to release the residual stress; S5, remove surface residues by ultrasonic cleaning.
2. The method for preparing a quartz ore inclusion detection sample at room temperature according to claim 1, characterized in that: During the optical screening stage, gas-liquid inclusions appear as cloud-like bright spots due to differences in refractive index, while solid inclusions appear as dark shadow areas with clear boundaries. A high-intensity flashlight can be optionally used to verify areas suspected of inclusions.
3. The method for preparing a quartz ore inclusion detection sample at room temperature according to claim 1, characterized in that: During the cutting stage, the thickness of the diamond-coated thin-blade saw blade is ≤0.5 mm, and the vibration amplitude of the mechanical vibration is controlled within 10 μm in combination with the shock-absorbing smooth propulsion base.
4. The method for preparing a quartz ore inclusion detection sample at room temperature according to claim 1, characterized in that: The specific steps of the three-stage chemical mechanical polishing include: A1, macro scratch removal using 75 μm, 54 μm, and 18 μm diamond grinding discs and RO water; A2, use 12.5 μm soft sandpaper to refine the surface; A3, the sample was atomically flattened using a fiber polishing pad with 9μm, 3μm, and 1μm diamond suspensions.
5. The method for preparing a quartz ore inclusion detection sample at room temperature according to claim 1, characterized in that: The following steps are also included: B1, adhere the polished surface to a glass slide with epoxy resin and heat cure at 70°C for 3-5 hours; B2, after cooling naturally to room temperature, repeat the polishing operation on the other untreated side; B3, remove surface residues through ultrasonic cleaning and complete double-sided processing.
6. The method for preparing a quartz ore inclusion detection sample at room temperature according to claim 5, characterized in that: The diamond-coated thin-edged saw blade cuts at a low rotation speed of 800-1200 rpm.
7. The method for preparing a quartz ore inclusion detection sample at room temperature according to claim 1, characterized in that: The water-based coolant is an aqueous solution containing polyethylene glycol.
8. The method for preparing a quartz ore inclusion detection sample at room temperature according to claim 1, characterized in that: The method uses a visible light screening module, which includes a 200-fold optical microscope, a rotatable stage and an ultraviolet LED light source, and observes the optical characteristics of the sample surface in real time through an eyepiece or a camera.
9. The method for preparing a quartz ore inclusion detection sample at room temperature according to claim 1, characterized in that: The saw blade spindle of the diamond-coated thin-edged saw blade is connected to a speed regulating motor through a belt drive, a smooth and stable guide rail base is installed at the bottom, and coolant pipelines are arranged along both sides of the saw blade.
10. The method for preparing a quartz ore inclusion detection sample at room temperature according to claim 1, characterized in that: The method is completed at room temperature, with energy consumption of ≤0.8kW / h and inclusion integrity rate of ≥89.5%.